(untitled) (Stylos, 2017)
Translating from different languages, and particularly from ancient Latin and Greek, can be approached from multiple perspectives and has been the focus of research for many scholars. On this occasion, we will consider it from a pedagogical perspective and the units of analysis will be concrete translations made for teaching purposes, to be used with beginners in secondary- and tertiary-level institutions. This presentation’s main objetive is to foster reflection and, subsequently, to the identification of the main problems that students face when translating texts from Latin and Greek. We will finally suggest possible solutions to overcome these difficulties.